Climate Change, Climatic Hazards and National Security of Nepal - Rawal, Prakash Bikram (Journal of APF Command and Staff College, 2023)
This article examines the impact of climate change on the national security of Nepal by studying secondary data from the Ministry of Home Affairs. The data covers the last five years and focuses on five climate hazards: flood, landslide, windstorm, forest fire, and avalanches. Through an analysis of the human and economic costs and the frequency of occurrence, the study identifies windstorms as an emerging threat to national security. The research highlights that climatic hazards are affecting Nepal's security, and the study particularly investigates their impacts in the past year. The human and economic costs caused by these climatic hazards were assessed based on factors such as: deaths, injuries, missing persons, affected families, destroyed houses, displaced sheds, and estimated monetary losses. The study indicates a fluctuation in the frequency and impacts of some climatic hazards due to climate change, with 2076 BS being the most destructive year. Traditional threats such as floods and landslides persist, while windstorms are increasingly becoming stronger. Additionally, the incidents of forest fires have risen in the last two years. Among the five hazards, avalanches seem to be the least destructive in terms of human and economic costs. The findings underscore the importance of addressing climate change to safeguard Nepal's national security.